The Moderating Role of Business Intelligence in the Relationship between Supply Chain Alliances and Sustainable Firm Performance within Emerging Economic Environment - Babatunde, Bayode Olusanya; Ayeni, Adebanji Adejuwon William; Fasanmi, Olumuyiwa Oladapo; Olawanle, Victor Ojo; Adekanmbi , John Ayodele; Babalola-Alabi, Bolatito Bolade (International Review of Management and Marketing, 2026)
This study examined how Business Intelligence (BI) moderates the relationship between Supply Chain Alliances (SCA) and Sustainable Firm Performance (SFP) in emerging economic environments. Adopting a quantitative design and structural equation modeling, the study assessed both the direct and moderating effects of BI on firm sustainability outcomes. Findings showed that supply chain alliances have a positive but modest influence on sustainable firm performance (β = 0.204, t = 2.979, p = 0.003). BI also exhibited a positive effect on SFP (β = 0.096, t = 1.006, p = 0.004), suggesting its independent relevance to sustainability enhancement. Crucially, BI demonstrated a strong moderating effect on the SCA–SFP relationship (β = 0.715, t = 8.835, p < 0.001), indicating that BI significantly strengthens the impact of supply chain partnerships on firm sustainability. This underscores BI as a vital factor of sustainable performance in emerging markets, enhancing the benefits derived from alliances through improved analytics, real-time insights, and informed decision-making. The study concludes that firms can achieve superior sustainability outcomes by integrating BI tools into their supply chain processes. It recommends greater investment in BI infrastructure, enhanced knowledge sharing among partners, and the development of analytical capabilities that incorporate environmental and market intelligence into sustainability strategies.